An Improved Method for the Determination of Airplane Radial Velocity Using Doppler Shift (Iraqi Journal of Physics, 2010)
In this research velocity of moving airplane from its recorded digital sound is introduced. The data of sound file is sliced into several frames using overlapping partitions. Then the array of each frame is transformed from time domain to frequency domain using Fourier Transform (FT). To determine the characteristic frequency of the sound, a moving window mechanics is used, the size of that window is made linearly proportional with the value of the tracked frequency. This proportionality is due to the existing linear relationship between the frequency and its Doppler shift. An algorithm was introduced to select the characteristic frequencies, this algorithm allocates the frequencies which satisfy the Doppler relation, beside that the tracked frequencies was chosen to be the most occurred frequencies in the power spectrum. Several sizes of the overlap windows have been tested to study the effect of window size on the accuracy of the determined radial velocity of the moving airplane.